A Framework for Implementing ISO 9000 and Total Quality Culture in Higher Education - Che Azlan bin Taib; Ahmed Hani Mohammed; Rosman Iteng; Halim Mad Lazim (International Journal of Supply Chain Management, 2018)
Abstract This paper presents a framework for implementing ISO 9000 total quality culture for Higher Education Institutions (HEIs). The understanding and practices level, as well as the relationship with organizational performance also presented. The preliminary data were collected through questionnaire approach, and respondent selection is based on simple random sampling methodology. A total of 73 (87.6%) valid data were analyzed. The result indicate 20% of the respondents do not understand or unsure about ISO 9000. From descriptive analysis and correlation coefficient testing, the study found the average level of understanding and practice levels is moderate. The coefficient correlation (r) indicates a strong relationship between the level of understanding and the level of practice for ISO 9000with r = .804, n = 73 (p.001). The study also disclosed that it is a significant correlation exists between the level of understanding QMS ISO 9000 and the level of practice, the value of r = 0.789 (p0.001). Finally, the study shows strong significant relationships between the level of understanding and practice of the achievement performance of UUM on the value of r =.796, (p .001). As a conclusion the awareness training is an essential to ensure the effectiveness of ISO 9000 Quality Management System(QMS) and total quality culture implementation.